Aspects of African traditional religion - Pobee, John S. (SA. Sociological Analysis, 1976)
The method of studying African traditional religion is first discussed and then the elements of the method guide an analysis of the Akan religion in West Africa according to their understanding of the Supreme Being, the ancestors, magic, witchcraft and various rites of passage.
free
Keywords: Akan (African people); Ancestor worship; Ghana – Religion; God (African religion)